2019
DOI: 10.1111/psyp.13322
|View full text |Cite
|
Sign up to set email alerts
|

Active information sampling varies across the cardiac cycle

Abstract: Perception and cognition oscillate with fluctuating bodily states. For example, visual processing has been shown to change with alternating cardiac phases. Here, we study the heartbeat's role for active information sampling-testing whether humans implicitly act upon their environment so that relevant signals appear during preferred cardiac phases. During the encoding period of a visual memory experiment, participants clicked through a set of emotional pictures to memorize them for a later recognition test. By … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 100 publications
6
46
0
Order By: Relevance
“…To examine whether or not there was a significant statistical relationship between the saccades, fixations, blinks, and the phase of the cardiac cycle, we calculated the phase of these oculomotor events as a function of the R-R interval (Kunzendorf et al, 2019). Circular statistics were employed in order to exploit the iterating nature of the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine whether or not there was a significant statistical relationship between the saccades, fixations, blinks, and the phase of the cardiac cycle, we calculated the phase of these oculomotor events as a function of the R-R interval (Kunzendorf et al, 2019). Circular statistics were employed in order to exploit the iterating nature of the cardiac cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Ohl and colleagues (2016) reported the generation of involuntary phase-locked microsaccades to the systolic phase of the cardiac cycle. Similarly, Kunzendorf et al, (2019) reported the generation of more keypresses, which led to the onset of images to-be-sampled, during the systolic phase. Here we tested the hypothesis that the timing of eye movements in a free visual search task would be modulated during the different phases of the cardiac cycle.…”
Section: Introductionmentioning
confidence: 92%
“…In both our present and our previous stop signal studies, we targeted the presentation of motor task cues according to timepoints when arterial baroreceptors -which underpin the neural and cognitive perception of a heartbeat -will be maximally active versus quiescent. Alternatively, one can study each individual participant's ECG post-hoc to either pinpoint whether stimuli fell into particular cardiac phases 19 , or bin trials into histogram plots 21 . It may be important to bear in mind such different methodological approaches in timing task events to specific points within the cardiac cycle when comparing cardiac timing effects across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Phase values belonging to the interval (-π, 0) were classified as expiration, whereas those in the interval (0, π) as inspiration. Systole and diastole of a heartbeat signal were defined as parts of a heartbeat cycle with previously defined onsets and durations relative to R peak (Kunzendorf et al, 2019).…”
Section: Respiration and Heartbeatmentioning
confidence: 99%